Development of air traffic simulation model - Chong, Kee Foong (2018)
In recent years, demands for air travel have been increasing. Countries are upgrading or building their airports to meet these growing demands. As the volume of air traffic increases, the work load of the air traffic controllers increases as well. This project aims to develop a software focusing on analysing air traffic controllers’ work load based on historical flight trajectories. The implementation utilises historical flight data from FlightAware. Using this data, the author runs it through a solver based on Non-dominated Sorting Genetic Algorithm II to get the coordinates of the Voronoi seeds of every hour. Upon obtaining the Voronoi seeds, a Voronoi diagram of each hour is calculated and overlaid onto a map of the Singapore Flight Information Region. The user can use a slider function to select the exact hour of data he wants to view. With some modifications to the application, it is possible for it to display and do real-time analysis of air traffic controllers’ workload.